2015
DOI: 10.1016/j.poly.2014.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Experimental measure of metal–alkynyl electronic structure interactions by photoelectron spectroscopy: (η5-C5H5)Ru(CO)2C CMe and [(η5-C5H5)Ru(CO)2]2(μ-C C)

Abstract: The gas-phase He I and He II photoelectron spectra of the propynylruthenium molecule CpRu(CO) 2 C≡CMe (Cp = η 5-C 5 H 5) and the ethynediyldiruthenium molecule [CpRu(CO) 2 ] 2 (µ-C≡C) are compared with the spectrum of CpRu(CO) 2 Cl to experimentally determine electronic structure interactions of the alkynyl ligands with the metal. The spectra indicate that the interaction between the filled metal-dπ and filled alkynyl-π orbitals dominates the metal-alkynyl π electronic structure, mirroring previously character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…They concluded that there is a mixing of ligand and metal orbitals leading to extended conjugation through the metal sites. They also showed that a band gap difference (Δ E g ) of 0.3–0.7 eV exists between the square planar Pt­(II) poly-ynes and corresponding model complexes. , Lichtenberger and co-workers carried out ultraweak photon emission (UPE) spectroscopic studies to understand the electronic interactions between Ru­(II) and alkynyl ligands. They found that in these complexes too, metal-alkynyl π electronic structure is mainly dominated by the interaction between the filled metal- d π and filled alkynyl-π orbitals.…”
Section: Structure–property Relationshipsmentioning
confidence: 99%
“…They concluded that there is a mixing of ligand and metal orbitals leading to extended conjugation through the metal sites. They also showed that a band gap difference (Δ E g ) of 0.3–0.7 eV exists between the square planar Pt­(II) poly-ynes and corresponding model complexes. , Lichtenberger and co-workers carried out ultraweak photon emission (UPE) spectroscopic studies to understand the electronic interactions between Ru­(II) and alkynyl ligands. They found that in these complexes too, metal-alkynyl π electronic structure is mainly dominated by the interaction between the filled metal- d π and filled alkynyl-π orbitals.…”
Section: Structure–property Relationshipsmentioning
confidence: 99%
“…Literature data indicate that BCl 2 – , and SiCl 3 – , , while being much poorer acceptors than CO, nonetheless are modest π acceptor ligands. Indeed, Lichtenberger et al argued that SiCl 3 – is a better π acceptor than CN – and CCH – , based on photoelectron spectroscopic studies of CpM­(CO) 2 (X) complexes (M = Fe, Ru) .…”
Section: Resultsmentioning
confidence: 99%
“…Literature data indicate that BCl 2 −45,46 and SiCl 3 − , 47,48 while being much poorer acceptors than CO, nonetheless are modest π acceptor ligands. Indeed, Lichtenberger et al argued that SiCl 3…”
mentioning
confidence: 99%
“…The effects of π backbonding appear in aspects of transition-metal coordination chemistry ranging from evaluation of orbital gaps and the spectrochemical series to the thermodynamic trans influence and the kinetic trans effect. A textbook example involves the trend in M­(CO) 6 q complexes where the extent of backbonding correlates with the carbon–oxygen vibrational stretching frequencies. Experimentally, evaluating relative amounts of π acceptor capacity for different ligand types has proved challenging, mostly because it is difficult to separate σ-bonding and π-bonding effects. Carbonyl carbon–oxygen vibrational stretching frequencies have been used to assess the π backbonding capacities of other ligands bound to the same metal, but care must be taken in selecting ligands, metals, and geometries to obtain trustworthy results. Lichtenberger and coworkers argued that gas-phase photoelectron spectroscopy is the only experimental technique that can quantitatively separate ligand π-bonding effects from σ-bonding and charge potential effects. , Using this technique, they found that CCH – acts as nearly a pure donor toward d 6 CpM­(CO) 2 (M = Fe and Ru) fragments rather than as an acceptor and that SiCl 3 – acts as a modest acceptor in these systems. Recently, Roithová, Rasika Dias, and coworkers used gas-phase bond dissociation to show that alkynes bind coinage metal complexes more strongly than alkenes do, a result they trace to greater backbonding in the former …”
Section: Introductionmentioning
confidence: 99%
“…7−13 Lichtenberger and coworkers argued that gas-phase photoelectron spectroscopy is the only experimental technique that can quantitatively separate ligand π-bonding effects from σ-bonding and charge potential effects. 14,15 Using this technique, they found that CCH − acts as nearly a pure donor toward d 6 CpM(CO) 2 (M = Fe and Ru) fragments rather than as an acceptor and that SiCl 3 − acts as a modest acceptor in these systems. Recently, Roithova, Rasika Dias, and coworkers used gas-phase bond dissociation to show that alkynes bind coinage metal complexes more strongly than alkenes do, a result they trace to greater backbonding in the former.…”
Section: ■ Introductionmentioning
confidence: 99%